Dataset about Warming Effects on Carbon Cycling and Greenhouse Gas Fluxes in Permafrost Ecosystems - Tao Bao (8583177) (2025)
This dataset compiles observation-based results on the impact of experimental warming on carbon cycles and greenhouse gas (GHG) fluxes in permafrost ecosystems. It integrates 1,430 independent warming experiments extracted from 132 peer-reviewed studies published between 1990 and 2024, covering eight major permafrost ecosystem types across the Northern Hemisphere. The dataset provides 17 variables including plant and soil carbon pools, soil nitrogen pools, and GHG fluxes (CO₂, CH₄, and N₂O), together with site information (latitude, longitude, altitude, ecosystem type, plant type, climate zone), climate conditions, and experimental design (warming method, magnitude, and duration). The following files are included: 1. “Data_Permafrost_Carbon.xlsx” includes the data. The “Dataset” sheet included data collected from 1430 pairs of observations from 132 published studies, while the “Readme” sheet contains descriptions of the abbreviations and variables within the dataset. 2. “Data_Meta.docx” includes a summary defining each column, trait collected in the data and the unit for each variable. 3. “Data_publications.docx” contains all the 132 references of the articles for the dataset. 4. “Code.rar” includes all the Python code for data scraping, site map plotting, data validation (funnel plots), and table data generation for this study. We will continue to update and improve the dataset, and encourage others to contribute new data to enhance its coverage. Newly published data will be added to this open-source dataset. This dataset can be used for meta-analyses and literature reviews to explore research frontiers in permafrost carbon-climate feedbacks. This dataset can also serve as observational data to assist in validating research findings based on remote sensing observations. Moreover, it could improve permafrost-related parameterization schemes in land models by providing empirical evidences for model calibration and validation.